Transport Direction and Scandinavian Source Regions of the Saalian Glacial and Glaciofluvial Deposits in a Case Study of Łubienica-Superunki (Central Poland) - Wachecka-Kotkowska, Lucyna; Górska-Zabielska, Maria; Smolska, Ewa (Minerals, 2021)
11 FINAL_PUBLISHED 7 AT_PUBLICATION Środki finansowe, o których mowa w art. 365 pkt. 2 ustawy